A new blind groundwater-dwelling genus of the Cladocera (Crustacea: Branchiopoda) from the Korean Peninsula - Jeong, Hyun Gi; Sinev, Artem Y.; Brancelj, Anton; Chang, Kwang-Hyeon; Kotov, Alexey A. (Zootaxa, 2017)
Groundwater-dwelling Cladocera are to date known only from the caves and hyporheic zones of the rivers in Europe (Belgium, England, France, Bosnia and Herzegovina, Macedonia, Slovenia, Spain), Turkey (European part) and Arabian Peninsula (Yemen). All these animals belong to the subfamily Aloninae Dybowski & Grochowski of the family Chydoridae Dybowski & Grochowski (Cladocera: Anomopoda). Examination of some samples collected by our colleagues — experts in Copepoda, Bathynellidae and Amphipoda—in South Korea led us to discovery of a new stygobiotic alonine genus, which is also the first record of a groundwater-dwelling cladoceran in Asia. Aims of this paper are: (1) to describe Korealona gen. nov., represented by two species, Korealona karanovici gen. nov., sp. nov. found in three different localities, and K. choi sp. nov., also found in three different localities; and (2) to discuss its differences from other genera of this subfamily and possible phylogenetic position of this genus among the aloninse. Distribution ranges of two species of Korealona gen. nov. are not unequivocally associated with present-day main river basins in Korea, but more sampling efforts are needed for final conclusions on their distribution ranges in Korea and closest countries and understanding of the genus evolutionary history.